2021
DOI: 10.1093/ornithapp/duaa068
|View full text |Cite
|
Sign up to set email alerts
|

Greater Sage-Grouse nest bowls buffer microclimate in a post-megafire landscape although effects on nest survival are marginal

Abstract: Temperature at fine spatial scales is an important driver of nest site selection for many avian species during the breeding season and can influence nest success. Sagebrush (Artemisia spp.) communities have areas with high levels of vegetation heterogeneity and high thermal variation; however, fire removes vegetation that provides protection from predators and extreme environmental conditions. To examine the influence of microclimates on Greater Sage-Grouse (Centrocercus urophasianus) nest site selection and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…Thus, the temporal lag we observed likely reflects the point at which the shrub canopy had returned to levels that fulfilled sage‐grouse life history needs for summer (<16.9%; Hagen et al, 2007) and winter (10%–30%; Hupp & Braun, 1989). Our findings support previous reports of the damaging effects of the loss of sagebrush on sage‐grouse space‐use and potentially population dynamics (Anthony et al, 2021; Dahlgren et al, 2010; Green et al, 2017; Smith & Beck, 2018; Walker et al, 2007, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the temporal lag we observed likely reflects the point at which the shrub canopy had returned to levels that fulfilled sage‐grouse life history needs for summer (<16.9%; Hagen et al, 2007) and winter (10%–30%; Hupp & Braun, 1989). Our findings support previous reports of the damaging effects of the loss of sagebrush on sage‐grouse space‐use and potentially population dynamics (Anthony et al, 2021; Dahlgren et al, 2010; Green et al, 2017; Smith & Beck, 2018; Walker et al, 2007, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of sage‐grouse has contracted by ~50%, with concurrent species‐level population declines, coinciding with the loss and degradation of sagebrush ecosystems (Knick & Connelly, 2011), which has made them the focal species of conservation and research of the sagebrush biome in recent years. Studies have reported negative effects of wildfire on the structure, function, or composition of sage‐grouse habitat and population demographics or growth (Anthony et al, 2020, 2021; Blomberg et al, 2012; Coates, Casazza, et al, 2016; Davis & Crawford, 2015; Foster et al, 2019; Nelle et al, 2000). Yet, few studies have examined how wildfire influences sage‐grouse habitat selection and space use (Byrne, 2002; Foster, 2016; Lockyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sage‐grouse response to fire has been investigated previously (e.g., Anthony et al, 2021 ; Lockyer et al, 2015 ), little information is available about how post‐fire restoration treatments affect patterns in resource selection by sage‐grouse. To address this information gap, we used telemetry data to evaluate habitat selection by sage‐grouse in each of 3 years after a large wildfire in sagebrush steppe in the Intermountain West.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of sagebrush cover (truex¯ = 2%) and high cheatgrass cover (truex¯ = 12%) provided low quality nesting habitat within burned Wyoming big sagebrush communities in our study area (Anthony et al, 2020). Despite these unfavorable nesting conditions, sage‐grouse selected fine‐scale vegetation features within burned areas, which provided thermal and concealment cover, a strategy which increased NS (Anthony et al, 2021).…”
Section: Discussionmentioning
confidence: 99%